Effect of Micro-nutrients Supplementation and Seasonal Variability on Production Performance, Antioxidants and Immune Status in Crossbred Heifers - Jain, Khushboo (Indian Journal of Animal Nutrition, 2021)
Twenty four Karan Fries crossbred heifers were allocated into 4 groups of 6 animals each to evaluate the effects of micronutrient supplementation on animal performance during summer and winter seasons.The animals were fed concentrate mixture, maize fodder and wheat straw to meet nutrient requirements (ICAR, 2013). In group G1, the mineral mixture added in concentrate mixture was devoid of iodine while in groups G2 and G3, iodine was supplemented at 0.25 and 0.5 ppm of diet. In group G4, a micro-nutrient mixture was supplemented that contained chromium, niacin, vitamin E and Zn at 1.5, 600, 40 and 40 ppm of dietary DM, respectively. Daily feed intake, body weight gain, feed conversion ratio were similar in different groups irrespective of seasons.Activities of glutathione peroxidase, super oxide dismutase and catalase did not vary due to treatments and seasons. However, overall ferric reducing ability of plasma values was reduced (P<0.05) in group G4 in both seasons and the values were lower (P<0.05) in winter than summer. The thiobarbuturic reactive substances values were also comparatively higher (P<0.01) in summer. Plasma total immunoglobulins concentration was higher (P<0.05) in winter irrespective of groups. Hence, micronutrient supplementation could help to mitigate oxidative stress in crossbred heifers during summer.